Learning the possible : Mexican American students moving from the margins of life to new ways of being - Reyes, Reynaldo, 1973- (University of Arizona Press, 2013)
In this book, the author demonstrates that it is possible for underprepared high school graduates to be successful in college. It chronicles the struggles and triumphs of five Mexican American students in their first year of college, aided by a one-year scholarship and support program called the College Assistance Migrant Program. CAMP, a federally funded program, is designed to help college students from migrant and/or economically disadvantaged families complete their first year of college. CAMP’s principal objective is to put students on a trajectory toward completion of a bachelor’s degree. Laura, Christina, Luz, Maria, and Ruben, as the author calls them, had daunting challenges: difficulties with English, extremely low self-confidence, teenage motherhood, conflict between gender roles and personal desires, and a history of gang membership. Focusing on the importance of constructing a new identity as a successful student, the author shares with readers the experiences of these marginalized students. Their stories, coupled with perspectives from instructors, CAMP staff and counselors, and the author’s own observations, illustrate the influence of past schooling, the persistence of culture, and the tensions and challenges inherent in developing a new identity.